2013
DOI: 10.2139/ssrn.2404290
|View full text |Cite
|
Sign up to set email alerts
|

The Real Costs of Corporate Credit Ratings

Abstract: Credit rating agencies emphasize the importance of specific financial ratio thresholds in their rating process. Firms on the favorable side of these thresholds are more likely to receive higher ratings than similar firms that are not. I show that firms near these salient thresholds respond to the incentive to improve their appearance on this dimension by distorting real investment activities during periods leading up to bond issuance. These firms are significantly more likely to reduce R&D and SG&A expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Focusing on credit analysts provides an interesting setting, because their expertise and career concerns should reduce the effect of partisan perception (e.g., Gentzkow, Glaeser, and Goldin (2006); Hong and Kacperczyk (2010)). At the same time, any effect of partisan perception on credit rating actions is likely to have implications for firms' cost of financing (Fracassi, Petry, and Tate (2016)), as well as their financial policy and investment decisions (Chernenko and Sunderam (2011); Begley (2015); Almeida, Cunha, Ferreira, and Restrepo (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on credit analysts provides an interesting setting, because their expertise and career concerns should reduce the effect of partisan perception (e.g., Gentzkow, Glaeser, and Goldin (2006); Hong and Kacperczyk (2010)). At the same time, any effect of partisan perception on credit rating actions is likely to have implications for firms' cost of financing (Fracassi, Petry, and Tate (2016)), as well as their financial policy and investment decisions (Chernenko and Sunderam (2011); Begley (2015); Almeida, Cunha, Ferreira, and Restrepo (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…The other studies found that firms near thresholds of EBITDA-based ratios are more likely to reduce R&D and SG&A expenditures (boosting EBITDA) prior to bond issuance (Begley, 2013). Also, firms with loan contracts that contain covenants based on EBITDA are more likely to misclassify core expenses as special items, in order to increase EBITDA (Fan et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms have lower thresholds for the level of their rating (Kisgen (2009)) and put more effort into preventing downgrades than into achieving upgrades by actively reducing leverage when their current credit rating level is threatened (Begley (2013)). Moreover, stock price reactions after downgrades announcements are more pronounced than after upgrades and a constant level of a credit rating conveys a stable financial situation and a low uncertainty about the level of a firm's risk (Ederington and Goh (1998)).…”
Section: I1 the Economic Framework For Estimating The Debt Capacitymentioning
confidence: 99%
“…We calculate the debt capacity as the critical debt ratio that triggers a downgrade in the creditworthiness of a firm. This debt ratio is of special relevance as firms have thresholds for their rating (Kisgen (2009)) and put high effort into preventing downgrades to convey a stable financial situation for future capital issues (Begley (2013)). Our definition of the debt capacity aims at identifying a critical debt ratio that firms try to avoid because exceeding this ratio leads to a downgrade which conveys negative information on the firm's financial 1 situation and results in negative shock to a firm's cost of capital.…”
mentioning
confidence: 99%